Regulation of Endothelial Progenitor Cell Functions in Ischemic Heart Disease: New Therapeutic Targets for Cardiac Remodeling and Repair - Huang, Huai; Huang, Weiqiang (Frontiers in Cardiovascular Medicine, 2022)
Ischemic heart disease (IHD) is the leading cause of morbidity and mortality worldwide. Ischemia and hypoxia following myocardial infarction (MI) cause subsequent cardiomyocyte (CM) loss, cardiac remodeling, and heart failure. Endothelial progenitor cells (EPCs) are involved in vasculogenesis, angiogenesis and paracrine effects and thus have important clinical value in alternative processes for repairing damaged hearts. In fact, this study showed that the endogenous repair of EPCs may not be limited to a single cell type. EPC interactions with cardiac cell populations and mesenchymal stem cells (MSCs) in ischemic heart disease can attenuate cardiac inflammation and oxidative stress in a microenvironment, regulate cell survival and apoptosis, nourish CMs, enhance mature neovascularization, alleviate adverse ventricular remodeling after infarction and enhance ventricular function. In this review, we introduce the definition and discuss the origin and biological characteristics of EPCs and summarize the mechanisms of EPC recruitment in ischemic heart disease. We focus on the crosstalk between EPCs and endothelial cells (ECs), smooth muscle cells (SMCs), CMs, cardiac fibroblasts (CFs), cardiac progenitor cells (CPCs), and MSCs during cardiac remodeling and repair. Finally, we discuss the translation of EPC therapy to the clinic and treatment strategies.